Discoloration of Bulk-Fill versus conventional composites : a spectrophotometric evaluation = Decoloración de resinas Bulk vs resinas convencionales : evaluación espectrofotométrica - Serin Kalay, Tugba (2021)
Purpose: The purpose of this study was to evaluate the discoloration of a dual-cure bulk-fill (DCBF) and light-cure bulk-fill (LCBF) composites relative to conventional composites (CC) after water and coffee immersion. Methods: One-hundred disc-shaped specimens (8mm in diameter × 4mm thickness) were prepared using five commercially available composites (n=10); two LCBF (XB-X-trafil Voco, FB-FiltekTM Bulk Fill), one DCBF (FU-Fill-upTM Coltene), and two CC (CE-Clearfil Majesty ES2, EQ-Estelite ΣQuick). Initial and final color readouts were measured with a spectrophotometer (Easyshade,Vita) according to the CIELAB color system. Statistical analyses were performed using 2-way ANOVA with Bonferroni adjustment to evaluate ΔE, ΔL, Δa, and Δb parameters (p<0.05). Results: Significant interactions were noted among the material types and immersion solutions for all evaluated parameters (p=0.00). ΔE values were observed in the order of FU>FB≥XB>EQ≥CE in water immersion groups and XB>FB>EQ≥FU≥CE in coffee immersion groups. Conclusion: Within the limitations of this study, DCBF composite is more susceptible to intrinsic discoloration compared to LCBF and CC. However, DCBF exhibited lower extrinsic discoloration than LCBF and comparable with CC after coffee immersion. Depending on their chemical and structural compositions, composites will exhibit color change, which compromises the esthetic performance of composite restorations.
Propósito: El propósito de este estudio fue evaluar la decoloración de resinas bulk de curado dual (DCBF) y bulk activadas por fotopolimerización (LCBF) en relación con las resinas convencionales (CC) después de la inmersión en agua y café. Métodos: Se prepararon cien muestras en forma de disco (8mm de diámetro × 4mm de espesor) utilizando cinco resinas compuestas disponibles comercialmente (n=10); dos LCBF (XB-X-trafil Voco, FB-FiltekTM Bulk Fill), un DCBF (FU-Fill-upTM Coltene) y dos CC (CE-Clearfil Majesty ES2, EQ-Estelite ΣQuick). Las lecturas de color inicial y final se midieron con un espectrofotómetro (Easyshade, Vita) de acuerdo con el sistema de color CIELAB. Los análisis estadísticos se realizaron utilizando ANOVA de 2 vías con ajuste de Bonferroni para evaluar los parámetros ΔE, ΔL, Δa y Δb (p<0,05). Resultados: Se observaron diferencias significativas entre los diferentes tipos de resina y las soluciones de inmersión para todos los parámetros evaluados (p=0,00). Se observaron valores de ΔE en el orden de FU>FB≥XB>EQ≥CE en los grupos de inmersión en agua y XB>FB>EQ≥FU≥CE en los grupos de inmersión en café. Conclusión: Dentro de las limitaciones de este estudio, la resina DCBF es más susceptible a la decoloración intrínseca en comparación con LCBF y CC. Sin embargo, DCBF mostró una decoloración extrínseca más baja que LCBF y comparable con CC después de la inmersión en café. Dependiendo de sus composiciones químicas y estructurales, los composites mostrarán cambios de color, lo que compromete el desempeño estético de las restauraciones de resinas con el tiempo.
En revista Odóvtos, vol. 23, no.2 (mayo-agosto 2021)
Descripción basada en el contenido visto el 08 de noviembre, 2024
También disponible en formato HTML y EPUB